基于Excite的双质量飞轮仿真分析 - 王远 (Jixie chuandong)
The structure and operational principle of dual mass flywheel are discussed,and torsional vibration of the speed gearbox input shaft is analysed. Then,the engine crankshaft train simulation model is established based on Excite,and at the same time,the simulation analysis is carried out. At last,simulation and test results show that the dual mass flywheel not only could effectively decrease speed irregularity of gearbox input shaft,but also promote vehicle comfort and reduce crankshaft torsional vibration.